An examination of the relationship between perceptions that cigarette smoking increases the severity of COVID-19 and reduction in smoking during the COVID-19 pandemic: Findings from the 2021 ITC Korea Survey - Hae-ryoung Chun; Geoffrey T. Fong; Shannon Gravely; Steve S. Xu; Anne C. K. Quah; Heewon Kang; Wonjeong Yoon; Hong G. Seo; Yeol Kim; Sungkyu Lee; Gil-yong Kim; Chang Bum Kang; et al. (Tobacco Induced Diseases)
Introduction This study examined whether Korean adults who smoked cigarettes during the COVID-19 pandemic decreased their smoking because of COVID-19, with a focus on whether perceptions of susceptibility and severity of COVID-19 disease were associated with reduced smoking.